# Rewrite Equations to Solve for Y

## Rewrite Equations to Solve for Y - How it Works - Video

Rewrite Equations to Solve for Y - How it Works - Video

**Example 1**

**Example 1**

Example 1:

We need to solve for y. Right now we have a coefficient of 3 and we need a coefficient of 1. So our first step is to divide both sides by 3.

3y = 2x + 6

y = (2x + 6)/3

y = 2/3 * x + 6/3

y = 2/3 *x + 2

Given

Divided both sides by 3

Separated into two fractions

Simplified

**Example 2**

**Example 2**

Example 2:

We need to solve for y. Right now we have a coefficient of 3 and we need a coefficient of 1. So our first step is to divide both sides by 3.

6x - 2y = 7

-2y = -6x + 7

y = -3x - 7/2

Given

Subtracted both sides by 6x

Divided each term by -2

## Live Worksheet

Live Worksheet